Targetted genome editing in yam (dioscorea spp.) using the crispr/Cas9 system - David, E.S. (University of Nairobi, 2021)
Yam is a starchy tuberous crop that provides food and income to millions of people in tropical and sub-tropical regions of the world. Despite its importance, several biotic and abiotic constraints beset yam production. Yam improvement by conventional breeding has been hampered by its polyploidy, heterozygosity, and vegetative propagation. Yam genetic improvement will therefore require the development of new techniques that allows direct manipulation of its genome. Targeted genome editing strategies such as zinc-finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs), and the clustered regularly interspersed short palindromic repeats (CRISPR/Cas) system have proven that sequence-specific nucleases are effective tools for use in gene function analysis and crop improvement. Compared to ZFNs and TALENS, the CRISPR system holds more potential due to its simplicity, efficiency, versatility and affordability. Plant genome engineering, however, relies on transformation and regeneration for the recovery of mutants. The production of embryogenic callus is a crucial step in the regeneration of most crops. This study reports a system for CRISPR/Cas9-mediated genome editing in yam. The conditions suitable for somatic embryogenesis, regeneration of friable embryogenic callus, and Agrobacterium mediated transformation of two yam species, D. alata and D. rotundata were determined. Further, a protocol for isolation, purification, and culture of D. rotundata protoplasts was established from mesophyll and callus tissues. Various factors, including tissue type, explant age, period of enzyme incubation, enzyme concentration, phytohormone combinations, concentration in the culture medium, were shown to influence the protoplast yield, viability, and regenerative capacity. Two guide RNAs targeting the yam phytoene desaturase (PDS) gene were designed, transfected onto a suitable plasmid to generate pCas9-gRNA-gfp-PDS, then to Agrobacterium strain EHA 105. The efficacy of the Cas9-gfp gene expression in yam was evaluated by agroinfiltration. An optimized agroinfiltration system was developed, consisting of the Agrobacterium strain EHA105 harboring pCas9_gRNA-PDS (OD600= 0.75), suspended in infiltration buffer supplemented with 400 μM acetosyringone, infiltered in fully expanded young leaves and heat shock treatment. The CRISPR/Cas9 plasmid was delivered to nodal explants through Agrobacterium-mediated transformation, and mutated events were regenerated by organogenesis. Transgene expression of the gfp tagged gene in these events was further confirmed by GFP fluorescence under UV light. Eight events were regenerated, among which one was green, while seven showed phenotypes of complete to variegated albinism. Leaves of transgenic plants emitted a bright fluorescence, while wild-type plants did not emit any fluorescence. All putative transgenic plants contained Cas9, as confirmed by PCR analysis. All seven mutant events showed indels at both gRNA1 and gRNA2 within 3-4 bp upstream of the PAM sequences. The indels consisted of a mixture of insertions, deletions, and substitutions of 1 to 59 base pairs. As expected, the green plant showed no mutation at either target site. The genome-editing efficiency was 83.3%. The yam regeneration, genetic transformation, and genome editing protocols developed in this study will provide opportunities for yam improvement. Overall, these results demonstrated that the CRISPR/Cas9 system can induce site-specific disruption of the PDS gene and generate stable phenotypic changes in yam. The findings reported herein offer new frontiers for gene function analysis and direct manipulation of the yam genome.